1995
DOI: 10.1002/ccd.1810360317
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous retrieval of a broken umbilical catheter from left atrium in a premature newborn

Abstract: A 30-week gestational age baby boy weighing 1,117 g born with cesarian section had a broken umbilical vein catheter lodged in the left superior pulmonary vein. We successfully retrieved the foreign body by percutaneous approach using a pigtail catheter and a snare wire under portable fluoroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Breakage and embolization of catheter fragments complicate removal of these lines. Previous reports have shown that these fragments can be removed with minimal risk [3][4][5]. One of our patients (case 2) had a fragment from the umbilical venous line, the distal tip of which was lodged in the left atrial appendage.…”
Section: Discussionmentioning
confidence: 93%
“…Breakage and embolization of catheter fragments complicate removal of these lines. Previous reports have shown that these fragments can be removed with minimal risk [3][4][5]. One of our patients (case 2) had a fragment from the umbilical venous line, the distal tip of which was lodged in the left atrial appendage.…”
Section: Discussionmentioning
confidence: 93%
“…Though there are few case reports available in the literature of surgical[3] and percutaneous retrieval[456789] of retained UVC from an infant, yet to the best of our knowledge, there are only anecdotes in the literature of percutaneous retrieval of umbilical venous catheter in less than one kg neonate. [1]…”
Section: Discussionmentioning
confidence: 99%
“…Retrieval of migrated central line is not an uncommon procedure. The procedure has been well described in preterm babies also [1][2][3][4] Snaring the line and pulling it into a sheath which is then pulled out of the body accomplishes this rather gratifying procedure. In addition, the migration usually does not lead to hemodynamic instability.…”
Section: Discussionmentioning
confidence: 99%